2015
DOI: 10.1016/j.ijrobp.2015.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Hypercellularity Components of Glioblastoma Identified by High b-Value Diffusion-Weighted Imaging

Abstract: Purpose Using conventional MRI for target definition, glioblastomas may receive inadequate radiation dose coverage of the nonenhanced hypercellular subvolume. This study aimed to develop a technique to identify the hypercellular components of GB by using high b-value DWI and to investigate its relationships with the prescribed 95%- isodose volume (PDV) and progression-free survival (PFS). Methods Twenty-one patients with glioblastoma underwent chemoradiotherapy post-resection/biopsy. RT treatment planning wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Although high b -values are beginning to be adopted in primary prostate tumors ( 10 , 15 ) and brain glioma ( 16 ), along with models to characterize cellularity and microstructure, these methods had not been studied in bone metastases, where microstructure differs. Microstructure methods in bone would be particularly valuable due to the challenge of acquiring histological information from these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although high b -values are beginning to be adopted in primary prostate tumors ( 10 , 15 ) and brain glioma ( 16 ), along with models to characterize cellularity and microstructure, these methods had not been studied in bone metastases, where microstructure differs. Microstructure methods in bone would be particularly valuable due to the challenge of acquiring histological information from these areas.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Journal vascular due to high degree of angiogenesis. 73,74 This may imply that GBM has higher blood content or higher μ a . In fact, with the observation at 650 nm, the current study showed that μ a was about three times higher in GBM than that in LGG [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As for head and neck squamous cell carcinoma (HNSCC), mean ADC has been identified as a prognostic factor particularly if derived from the high b -value range only, whereas mean ADC could not be related to outcome if derived from low b -values only [44] , [30] . Moreover, several studies show that mean pre-treatment ADC is of predictive value for neoadjuvant radiochemotherapy response in rectal cancer [45] , [46] , [47] as well as a prognostic factor for progression-free survival in glioblastoma [48] . In cervical cancer, low mean pre-treatment ADC has been associated with good outcome [49] , whereas the opposite relationship has also been reported [50] .…”
Section: Potential Benefits Of Dwi For Rtmentioning
confidence: 99%